Geoinformatics 2006. 28-29 October, 2006, Wuhan, China - Li, Deren, 1939-; Xia, Linyuan; Wuhan da xue; Ce hui yao gan xin xi gong cheng guo jia zhong dian shi yan shi; Association of Chinese Professionals in Geographic Information Systems (Abroad); Guo jia zi ran ke xue ji jin wei yuan hui (China) (New York, NY : SPIE, 2006)
Includes bibliographical references and author index